RiceAntherNet: a gene co-expression network for identifying anther and pollen development genes - Lin, Hong; Yu, Jing; Pearce, Simon; Zhang, Dabing; Wilson, Zoe A. (Wiley, 2017)
In plants, normal anther and pollen development involves many important biological events and complex molecular regulatory coordination. Understanding gene regulatory relationships during male reproductive development is essential for fundamental biology and crop breeding. In this work, we developed a rice gene coexpression network for anther development (RiceAntherNet) that allows prediction of gene regulatory relationships during pollen development. RiceAntherNet was generated from 57 rice anther tissue microarrays across all developmental stages. The microarray datasets from 9 rice male sterile mutants, including msp1-4, ostdl1a, gamyb-2, tip2, udt1-1, tdr, eat1-1, ptc1 and mads3-4, were used to explore and test the network. Among the changed genes, three clades showing differential expression patterns were constructed to identify genes associated with pollen formation. Many of these have known roles in pollen development, for example 7 genes in Clade 1 (OsABCG15, OsLAP5, OsLAP6, DPW, CYP703A3, OsNP1 and OsCP1) are involved in rice pollen wall formation. Furthermore, Clade 1 contained 12 genes whose predicted orthologs in Arabidopsis have been reported as key during pollen development and may play similar roles in rice. Genes in Clade 2 are expressed earlier than Clade 1 (anther stages 2-9), while genes in Clade 3 are expressed later (stages 10-12). RiceAntherNet serves as a valuable tool for identifying novel genes during plant anther and pollen development. A website is provided (https://www.cpib.ac.uk/anther/riceindex.html) to present the expression profiles for gene characterisation. This will assist in determining the key relationships between genes, thus enabling characterization of critical genes associated with anther and pollen regulatory networks.